An integrative approach of the use of recycled concrete aggregate in high-rise buildings: Example of the Elysium - Ulucan, Muhammed; Alyamac, Kursat Esat (Ernst & Sohn, 2023)
The primary purpose of this study is to examine in detail the mechanical, environmental, and economic properties of concrete produced using recycled concrete aggregate (RCA) in different ratios. This study used RCAs obtained from construction and demolition wastes (CDW) that emerged after the 24 January 2020 Sivrice-Elazig earthquake to produce recycled aggregate concretes. The ultimate aim of this study is to determine the advantages and disadvantages of these structures in terms of mechanical, environmental, and economic properties if RCA will be used at certain rates in high-rise private buildings built with natural aggregate concrete (NAC) in Elazig. For this purpose, concretes with all natural aggregates, all recycled aggregates, and both natural aggregates and recycled aggregates were produced. A mathematical model was developed using response surface method to predict the mechanical properties of recycled coarse aggregate concretes (RCACs) by utilizing the compressive strength values of the produced concretes. Then, the component amounts of RCACs, which have the same compressive strength as the compressive strength values of the NAC used in Elysium, which was chosen as a sample building in Elazig, were estimated. Considering the estimated component amounts, environmental impact assessments and feasibility analyses were made according to four different scenarios, including parameters such as cement amount, chemical additive amount, the cost difference between RCA-natural coarse aggregate, and transportation distance. As a result of these evaluations and analyses, it was foresighted that using RCA would provide significant advantages in buildings produced using large amounts of concrete. This foresight is exemplified by the Elysium buildings. As a result, it was determined that the use of RCAs is appropriate, especially the concrete produced with aggregates obtained from CDW is more important for a sustainable environment, and the use of RCAs in high-rise buildings built using large amounts of concrete can provide significant environmental and economic advantages.
Keywords: construction and demolition waste; earthquake; high-rise buildings; life cycle assessment; recycled concrete aggregate; sustainable development